Local wisdom of Mapag Cai tradition of Banceuy villages indigenous community for sociology learning outcomes - Irra Martiana; Dian Peniasian (Inovasi Kurikulum, 2024)
This research aims to apply the value of Gotong royong as local wisdom of Mapag Cai tradition in the Banceuy Village Indigenous Community to be a commodity of wisdom value development in the educational scene of Sociology learning. This research was conducted as an effort to utilize local wisdom so that students understand the meaning of “gotong royong” and strengthen the ties of social interaction in the digital era, which causes indirect interaction that impacts students' interpersonal intelligence. This research uses a descriptive research method that is precise to the characteristics of Mapag Cai social activities. The research was conducted through direct observation and interviewing Banceuy Indigenous Community Leaders, literature studies, and other sources relevant to the writing topic. The results illustrate that the Mapag Cai tradition means the spirit of cooperation and solidarity in maintaining the cleanliness of irrigation channels based on the values and rules held firmly by residents, which can be an inspiration for learning with a contextual approach in building soft skills to foster the spirit of cooperation and social interaction between students.   Abstrak Penelitian ini bertujuan menerapkan nilai gotong royong sebagai kearifan lokal tradisi Mapag Cai di Kampung Adat Banceuy Desa Sanca, Kecamatan Ciater Kabupaten Subang menjadi komoditas pengembangan nilai kearifan dalam adegan pendidikan pembelajaran Sosiologi. Alasan penelitian ini dilakukan adalah sebagai upaya memanfaatkan kearifan lokal agar peserta didik memahami makna gotong royong dan memperkuat jalinan interaksi sosial di era digital yang menyebabkan tingginya interaksi tidak langsung sehingga membawa dampak terhadap kecerdasan interpersonal peserta didik. Penelitian ini menggunakan metode penelitian yang bersifat deskriptif secara tepat terhadap sifat-sifat kegiatan sosial Mapag Cai. Penelitian dilakukan melalui observasi langsung dan mewawancarai Tokoh Masyarakat Adat Banceuy serta studi pustaka dan sumber lain yang relevan dengan topik penulisan. Hasil penelitian menggambarkan tradisi Mapag Cai bermakna semangat gotong royong dan solidaritas dalam menjaga kebersihan saluran irigasi yang dilandasi oleh nilai dan tata aturan yang dipegang teguh warga dapat menjadi inspirasi pembelajaran dengan pendekatan kontekstual dalam membangun soft skill guna menumbuhkan semangat gotong royong dan interaksi sosial antar peserta didik. Kata Kunci: Kampung adat banceuy; pendidikan; gotong royong; kearifan lokal; mapag cai